Improving Community Welfare Through Community-Based Ecotourism Development in Banyu Biru Tourism Area, Pasuruan - Purwaningrm Puji Lestari; Nurhayati, Dies; Taufiq, Mochamad (Sumber Belajar Sejahtera, 2025)
Ecotourism is increasingly recognized as a sustainable tourism model that integrates environmental conservation with community empowerment. Banyu Biru, a natural spring located in Sumberejo Village, Pasuruan Regency, offers significant ecological, cultural, and historical value. However, this potential remains underutilized due to limited infrastructure, low community involvement, and lack of diversified tourism services. This study aims to explore the potential and challenges of developing community-based ecotourism in Banyu Biru and to formulate strategies to enhance local welfare through sustainable tourism practices. This research employed a qualitative descriptive method supported by a SWOT analysis framework. Data were collected through interviews, field observations, and questionnaires involving 100 community respondents over a one-month research period. The analysis identified internal strengths such as natural resources and cultural assets, as well as weaknesses including poor infrastructure and minimal tourism diversification. External opportunities such as increased demand for nature-based tourism and government support were also observed, along with threats like environmental degradation and regional competition. Findings reveal that the implementation of a community-based ecotourism strategy has led to increased community income, the emergence of micro-enterprises, and growing local awareness about environmental and cultural preservation. Despite these positive developments, only 62% of respondents experienced direct economic benefits, indicating the need for more inclusive planning. In conclusion, Banyu Biru holds promising potential as a model for sustainable, community-driven ecotourism. Strategic interventions focusing on infrastructure, local participation, and product diversification are essential to ensure long-term socio-economic and ecological impact.